2012
DOI: 10.1109/jmems.2012.2209405
|View full text |Cite
|
Sign up to set email alerts
|

Resonant PZT MEMS Scanner for High-Resolution Displays

Abstract: Abstract-A resonant piezoelectric scanner is developed for high-resolution laser-scanning displays. A novel actuation scheme combines the principle of mechanical amplification with lead zirconate titanate (PZT) thin-film actuation. Sinusoidal actuation with 24 V at the mechanical resonance frequency of 40 kHz provides an optical scan angle of 38.5• for the 1.4-mm-wide mirror. This scanner is a significant step toward achieving full-highdefinition resolution (1920 × 1080 pixels) in mobile laser projectors witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 32 publications
1
61
0
Order By: Relevance
“…Contrary to the DLP technology in which majority of the tasks for image production are realized optically, electronic design plays a more important role for scanning-type projectors. As demonstrated in prior studies, micro-scanning mirrors may be driven by electrostatic [5][6][7][8][9][10][11][12][13][14], electromagnetic [15][16][17][18] or piezoelectric [19][20][21][22][23] mechanisms. Each approach has its own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Contrary to the DLP technology in which majority of the tasks for image production are realized optically, electronic design plays a more important role for scanning-type projectors. As demonstrated in prior studies, micro-scanning mirrors may be driven by electrostatic [5][6][7][8][9][10][11][12][13][14], electromagnetic [15][16][17][18] or piezoelectric [19][20][21][22][23] mechanisms. Each approach has its own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 82%
“…Few studies have demonstrated micro-scanning mirrors with on-chip capacitive [12][13], piezoresistive [14] and piezoelectric [21] sensing capabilities. Drabe et al [14] reported a bi-axial electrostatic scanning mirror with piezoresistive sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scanner used in a previous research for actuation was 3.75 × 6.15 mm 2 , to actuate a 1.4 mm inner mirror frame. 13) Therefore, to realize a higher quality MEMS mirror, the die size of the actuator must reach the centimeter order.…”
Section: Large Mems Structuresmentioning
confidence: 99%
“…It is connected to the outer frame through flexures. The outer frame is 90° rotated with respect to the inner frame and can tilt about its longitudinal axis which is perpendicular to the inner frame tilting axis [9][10][11][12]. These types of structures are usually of larger size compared to gimbal-less structures, and consume larger power in operation.…”
Section: Introductionmentioning
confidence: 99%